Advances in human factors, business management and leadership : proceedings of the AHFE 2020 Virtual Conferences on Human Factors, Business Management and Society, and Human Factors in Management and Leadership, July 16-20, 2020, USA /: proceedings of the AHFE 2020 Virtual Conferences on Human Factors, Business Management and Society, and Human Factors in Management and Leadership, July 16-20, 2020, USA. (2020) - Unknown
No abstract available